Fiscal devaluation in a monetary union - Philipp Engler; Giovanni Ganelli; Juha Tervala; Simon Voigts (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
Between 1999 and the onset of the economic crisis in 2008 real ex-change rates in Greece, Ireland, Italy, Portugal and Spain appreciated relative to the rest of the euro area. This divergence in competitiveness was reflected in the emergence of current account imbalances. Given that exchange rate devaluations are no longer available in a monetary union, one potential way to address such imbalances is through a fiscal devaluation. We use a DSGE model calibrated to the euro area to investigate the impact of a fiscal devaluation, modeled as a revenue-neutral shift from employers' social contributions to the Value Added Tax. We find that a fiscal devaluation carried out in 'Southern European countries' has a strong positive effect on output, but a mild effect on the trade balance of these countries. In addition, the negative effect on 'Central-Northern countries' output is weak.
Keywords: E32; E62; F32; F41; 330; Fiscal Devaluation; Fiscal Policy; euro area; currency union; current account